2003
DOI: 10.1381/096089203322190862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rapid Weight Reduction on Risk of Cholelithiasis after Bariatric Surgery

Abstract: This study confirms the high correlation between morbid obesity, rapid weight loss and gallbladder disease. Predictive risk factors for gallstone formation were not found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(70 citation statements)
references
References 12 publications
3
64
0
3
Order By: Relevance
“…In addition to obesity as a well-known factor for development of cholelithiasis, rapid weight loss and altered GB function after bariatric surgery is associated with an even greater risk (2,3,9,11). Within the first two years after bariatric surgery, up to 50% of the patients develop gallstones or biliary sludge, although most of them are asymptomatic (11,12). Therefore, cholecystectomy is often required in obese people, but timing still remains controversial (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to obesity as a well-known factor for development of cholelithiasis, rapid weight loss and altered GB function after bariatric surgery is associated with an even greater risk (2,3,9,11). Within the first two years after bariatric surgery, up to 50% of the patients develop gallstones or biliary sludge, although most of them are asymptomatic (11,12). Therefore, cholecystectomy is often required in obese people, but timing still remains controversial (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Following bariatric surgery, especially Roux-en-Y gastric bypass (RYGB), the frequency of gallstone formation increases as compared to the normal population due to rapid weight loss (3,4). Hepatic supersaturation of bile with cholesterol, gallbladder stasis, and increased concentration of mucin within bile are possible causes (5).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cholelithiasis, symptomatic or not, is directly correlated to the body mass index (BMI) [6,[8][9][10]. Additionally, it has been clearly shown that periods of rapid weight loss further enhance the risk of cholesterol cholelithiasis [11][12][13]. In order to reduce the risk of gallstone formation and its complications, policies of routine prophylactic cholecystectomy [6], use of intra-operative ultrasound for gallstone detection and concomitant cholecystectomy [12,14,15], postoperative use of ursodeoxycholic acid [15,16], regular ultrasound surveillance for asymptomatic gallstone [12,[14][15][16], and their combinations have been suggested.…”
Section: Introductionmentioning
confidence: 99%